Diffusion-weighted imaging lesions after endovascular treatment of cerebral aneurysms: A network meta-analysis - Mo, Lijuan; Yue, Jianhe; Yu, Wanli; Liu, Xi; Tan, Changhong; Peng, Wuxue; Ding, Xueying; Chen, Lifen (Frontiers in Surgery, 2023)
Abstract Background: Thromboembolism is one of the common complications in endovascular treatments, including coiling alone, stent-assistant coiling (SAC), balloon-assistant coiling (BAC) and flow diverter (FD) stents, are widely used in treating intracranial aneurysms (IAs), which usually presents positive lesion in diffusion-weighted imaging (DWI). Whether these adjunctive techniques increase postprocedural DWI-positive lesions in endovascular treatment is unclear. Methods: A systematic electronic search was performed in PubMed, Medline and EMBASE for literature published from 2000 to October 2022, with language restricted to English. Eighteen studies (3 cohort studies and 15 case-control studies) involving a total of 1843 patients with unruptured IAs (UIAs) were included. We performed a frequentist framework network meta-analysis (NMA) to compare and rank risks of cerebral thromboembolism of the four endovascular treatments. Incoherence test was used to analyze the statistical disagreement between direct and indirect evidence. Funnel plot was conducted to analyze the publication bias. Results: DWI lesions incidence of FD stents, SAC, BAC and coiling alone are 66.1% (109/165), 37.6% (299/795), 31.1% (236/759), and 25.6% (236/921), respectively. Patients treated with FD stents have highest incidence of DWI-lesions than SAC (OR:2.40; 95%CI (1.15,5.00), P<0.05), BAC (OR:2.62; 95%CI (1.19,5.77), P<0.05), and coiling alone (OR 2.77; 95%CI (1.26,6.07), P<0.05). Incoherence test showed preferable consistence in this NMA. No obvious publication bias was found in funnel plot. Conclusion: FD stents placement tend to bring more ischemic lesions identified by DWI than any of other procedures for patients with UIA; the characteristics of FD stents may result in a higher DWI-lesions incidence.